Inhibition of the type III secretion system by syringaldehyde protects mice from Salmonella enterica serovar Typhimurium - Lv, Qianghua (J Cell Mol Med, 2019)
The invasiveness of Salmonella enterica serovar Typhimurium (S. Typhimurium) is closely associated with the Salmonella pathogenicity island (SPI)‐encoded type Ⅲ secretion system (T3SS), which can directly inject a series of effector proteins into eukaryotic cells to enable bacterial infection. In this study, syringaldehyde was identified as an effective inhibitor of the S. Typhimurium T3SS using an effector protein‐lactamase fusion reporter system. Syringaldehyde treatment could inhibit the expression of important effector proteins (SipA, SipB and SipC) at a concentration of 0.18 mM without affecting bacterial growth. Additionally, significant inhibition of bacterial invasion and cellular injury was observed following the syringaldehyde treatment in the co‐infection system of HeLa cells and S. Typhimurium. Furthermore, treatment with syringaldehyde provided systemic protection to mice infected with S. Typhimurium, reducing mortality (40.00%) and bacterial loads and relieving caecal damage and systemic inflammation. The results presented in this study indicate that syringaldehyde significantly affects T3SS activity and is a potential leading compound for treating S. Typhimurium infections.